(untitled) (Revista Electrónica REDINE, 2021)
The purpose of this research was to carry out an introspective process where the observation, conscious deliberation and epistemic accompaniment of authors versed in the art of pedagogy would meet to highlight the aspects that lead the teacher to manage reflective processes as part of the construction of significant precepts of their pedagogical practice; That is why it was taken as a fundamental element of information, a phenomenon that generated the massive need to transform human reality throughout the world; we talk about the COVID-19 pandemic; Therefore, to give substance to this essay, the beginning was detailing the importance of estimating the intrinsic and extrinsic processes that originate from everyday life since, during pedagogical practice, the teacher is sensitive to significant changes in professional behavior due to the social interaction, of physiological, psychological, social factors and finally by the accumulation of experience in the profession and in itself allow him to resignify through reflective processes his conception of the profession; secondly, it is reported how these influences affect the psyche of the teacher and then lead him to manage identity restructuring processes to be able to solve the needs of the community he serves, on the other hand, the challenges that Teachers face at this time because of the pandemic that is affecting the whole world and the little preparation to face it and finally the value of the teacher is recognized, who turns out to be able to adapt their pedagogical practice and adapt it in adverse situations.